Level of agro-based website surfing among Malaysian agricultural entreprenuers: a case of Malaysia - Mohamed Shaffril, Hayrol Azril; Hassan, Md. Salleh; Abu Samah, Bahaman (Friends Science Publishers, 2009)
The main objective of this study was to identify the level of agro-based website surfing among Malaysian agro-based entrepreneurs and factors affecting it. A total of 450 respondents were selected for this study from six fields of agro-based industry namely food processing, non-food processing, farming, plantation, fisheries and animal rearing. The sample list was gained from three agencies including Department of Agriculture Malaysia (DOA), Farmers Organization Authority (FOA) and Agro Bank of Malaysia. Data were collected using face to face interview method. Results revealed that level of agro-based website surfing among Malaysian agricultural entreprenuers was at low level, while the official website of Department of Agriculture Malaysia (DOA) (www.agrolink.moa.my/doa) was the most surfed website followed by the official website of Malaysian Agriculture Research and Development Institute (MARDI) (www.mardi.my) and the official website of Federal Agriculture Marketing Authority (FAMA) www.agrolink.moa.my/fama). Based on the t-test and ANOVA test done there was significance difference in agro-based website surfing in respondent’s gender, level of education and age.